2018
DOI: 10.3390/su10051492
|View full text |Cite
|
Sign up to set email alerts
|

Oleotourism: Local Actors for Local Tourism Development

Abstract: Abstract:Olive oil consumption has grown substantially in recent years, due in part to the fact that olive oil is healthy. Much of the global olive oil production comes from the rural areas of Jaén in southern Spain. Surrounding this industry, services such as oleotourism are increasing. This paper aims to identify the key elements supporting the development of oleotourism. After a preliminary exploratory analysis of the existing data, a qualitative analysis was performed with actors directly involved in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 49 publications
0
14
0
8
Order By: Relevance
“…The literature that exists until now has broadly described the motivations for diversification and the benefits that OOT has for companies and producers of olive oil. In parallel, the literature has highlighted some of the elements that constitute this tourism activity since its beginnings, or the potential that OOT could have in specific cases such as in Spain (Quesada et al., 2010), in Argentina (Elias and Barbero, 2017) and/or in Jaén (Tregua, D'Auria and Marano-Marcolini, 2018).…”
Section: The Concept Of Olive-oil Tourismmentioning
confidence: 99%
“…The literature that exists until now has broadly described the motivations for diversification and the benefits that OOT has for companies and producers of olive oil. In parallel, the literature has highlighted some of the elements that constitute this tourism activity since its beginnings, or the potential that OOT could have in specific cases such as in Spain (Quesada et al., 2010), in Argentina (Elias and Barbero, 2017) and/or in Jaén (Tregua, D'Auria and Marano-Marcolini, 2018).…”
Section: The Concept Of Olive-oil Tourismmentioning
confidence: 99%
“…La vinculación del oleoturismo a las zonas rurales es uno de los puntos que más se han tratado en la literatura y, aparte de tratarse de un agente diversificador de la economía, éste posee un elevado potencial para el desarrollo territorial (Tregua, D'Auria, Marano-Marcolini, 2018), movilizando el capital humano y repartiendo mejor los recursos en las zonas rurales. Asimismo, su puesta en marcha contribuye a la revalorización de antiguas instalaciones, que son rehabilitadas para su uso turístico, y a la recuperación de las tradiciones, que, debido al paso de los años y la industrialización, empezaban a perderse.…”
Section: Revisión De La Literaturaunclassified
“…Istražena je ponuda maslinarskog turizma u regiji Jaén, Španjolska, a glavne smjernice za budući razvoj su potreba uključivanja maslinarskog turizma u svakidašnji život lokalnog stanovništva, proizvođača maslinova ulja, u strategiju razvoja lokalne samouprave te potrebu stvaranja specifične marke, s ciljem osnaživanja slike maslinarskog turizma regije (Tregua et al, 2018). U okviru ponude maslinarskog turizma analizirana je važnost gastronomskog muzeja maslinova ulja u Turskoj kao jednog od načina zaštite, očuvanja i promocije kulturne baštine koja pridonosi gastronomskom turizmu i ističe gospodarsku vrijednost kulturnog nasljeđa zemlje (Sahini i Aydin, 2017).…”
Section: Maslinici 3648 Haunclassified
“…A research analysed the offer of olive tourism in the Jaén region, Spain, and the identified main guidelines for future development were the need to incorporate olive tourism into the daily life of the local population, olive oil producers, the local government development strategy, and the need to create a specific brand to empower the image of olive tourism (Tregua et al, 2018). As part of the olive tourism offer, a research analysed the importance of the gastronomic museum of olive oil in Turkey as one of the ways to protect, preserve and promote cultural heritage, which contributes to gastronomic tourism and assigns economic value to the country's cultural heritage (Sahini and Aydin, 2017).…”
Section: Maslinici 3648 Hamentioning
confidence: 99%